2013
DOI: 10.1097/meg.0b013e3283614ae1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically assisted percutaneous transesophageal gastrotubing

Abstract: Endoscopically assisted PTEG is a feasible, safe, and useful procedure. The use of endoscopy enhances visual information, may increase the safety of the procedure, and allows better confirmation of each step involved, without radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Other major techniques used for gastrostomy include percutaneous endoscopic gastrostomy (PEG) and surgical techniques such as laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) or percutaneous transesophageal gastrostomy (PTEG). 6 A comparison of PEG and surgical gastrostomy outcomes by Bravo et al 7 found no significant differences in mortality, major complications, or minor complications, apart from a subgroup analysis of randomised studies that slightly favoured PEG. Considering the relatively lesser expense of RIG and PEG, LAPEG would be best suited as a second-line approach for patients with unfavourable anatomy and for correction of suboptimal gastrostomy placement, as reported by Lodin et al 8 PTEG plays an important role when patients have contraindications to more standard methods of enteral access, such as massive ascites, peritoneal carcinomatosis, or difficult anatomy due to a hostile abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Other major techniques used for gastrostomy include percutaneous endoscopic gastrostomy (PEG) and surgical techniques such as laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) or percutaneous transesophageal gastrostomy (PTEG). 6 A comparison of PEG and surgical gastrostomy outcomes by Bravo et al 7 found no significant differences in mortality, major complications, or minor complications, apart from a subgroup analysis of randomised studies that slightly favoured PEG. Considering the relatively lesser expense of RIG and PEG, LAPEG would be best suited as a second-line approach for patients with unfavourable anatomy and for correction of suboptimal gastrostomy placement, as reported by Lodin et al 8 PTEG plays an important role when patients have contraindications to more standard methods of enteral access, such as massive ascites, peritoneal carcinomatosis, or difficult anatomy due to a hostile abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is usually executed with the use of ultrasonography combined with fluoroscopy but can also be performed using ultrasonography with endoscopic assistance. 17 Apart from overcoming some of the contraindications of PEG and possible adverse events from D-PEJ, PTEG may also offer some advantages over standard gastrostomy tube feeding. First of all, because the puncture site (esophagostomy site) is relatively distant from the tip of the inserted feeding tube, it is possible to start enteral feeding immediately after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…All of the procedures were performed using similar methods, as have been previously described (28), except that we used an esophageal balloon catheter (Boston Scientific, Marlborough, MA, USA) due to the unavailability of an RFB. The location of the cervical esophagus was evaluated by computed tomography (CT) before the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…PTEG was first described by Oishi et al in 1994 for patients without appropriate transabdominal access, and they developed the PTEG kits (Sumitomo Bakelite, Tokyo, Japan) including the needle, guide wire, rupture-free balloon (RFB), 16-Fr peel away sheath, and tubes (1). The RFB is the crucial material for this procedure and most studies regarding PTEG used this kit (2)(3)(4)(5)(6)(7)(8). Unfortunately, the complete PTEG kits are generally not available in most interventional radiology inventories.…”
Section: Introductionmentioning
confidence: 99%